ANALISA SISTEM KERJA MESIN PENGGILING EMPING JAGUNG DENGAN SISTEM DOUBLE ROLLER KAPASITAS 100 KG/JAM - Hasahari, Ali Fahmi; SAM, M Danny; Eswanto, E (MEKANIK: Jurnal Ilmiah Teknik Mesin, 2017)
Corn chips grinding machine is a machine that is used to grind and flatten corn to become corn chips, with a rotary grinding and piping roller movement, this machine is planned to have a capacity of 100 kg / f am, this test is to determine the production capacity, quality of piping hash, productivity analysis and variation in distance when selecting corn chips from the test results there is a 24 rpm rotation with a 2 mm piping roller distance obtained a capacity of 144 kg / hour with a production power of 5.36 watts / kg, at round 24 with a 3.5 mm piping roller distance obtained a maximum capacity of 122 kg / hour with engine productivity power of 6.33 watts / kg, 24 rpm pwda piwaran with jarctlc 5 mm piping roller obtained a maximum capacity of 133 kg / hour with a 633 watt / kg engine production capacity. the capacity obtained by empingfagung grinding machine is different due to the difference in time when testing start and first 29.69 second trial seconds 29.52 seconds, and the third experiment 32.58 the quality of piping is 79.5% at the distance of the piping roller piping is 77.5% on 3.8 mm piping roller distance, 82.5% kwalitasii on 5mm piping roller distance.